Qualitative analysis of human movement - Knudson, D. V. (Human Kinetics, 2013)
Third Edition. For sport science professionals, qualitative movement diagnosis (QMD) is a critical skill in helping individuals improve performance or reduce injury risk. This new edition focuses on the processes behind movement observation, assessment and diagnosis, emphasising how to recognise and correct errors in human movement. It enables anyone working in professions related to human movement to integrate and apply knowledge from the fields of sport movement, allied health and biomechanics to help their clients, patients or athletes improve their movement performance or move with a lower risk of injury. It provides students, teachers and researchers with a practical diagnostic framework, tutorials to guide them through the QMD process, advice on capturing relevant information from motor performances and descriptions of intervention strategies. Exploring the the processes behind assessment and diagnosis of movement technique. Duane V. Knudson, is a professor and chair of the Department of Health and Human Performance at Texas State University. He co-authored the first text on QMD, Qualitative Analysis of Human Movement, which has been translated into five languages. He has also published over 70 peer-reviewed articles in journals. Inhaltsverzeichnis: Part I. An Integrated Approach to Qualitative Movement Diagnosis; Chapter 1. Interdisciplinary Nature of Qualitative Movement Diagnosis; Chapter 3. Role of the Senses and Perception in Qualitative Movement Diagnosis; Part II. Four Tasks in the Diagnosis and Improvement of Human Movement; Chapter 4. Preparation: Gathering Relevant Knowledge; Chapter 7. Intervention: Strategies for Improving Performance; Part III. Practical Applications of Human Movement Diagnosis; Chapter 8. Video Replay Within Qualitative Movement Diagnosis; Chapter 10. Theory-Into-Practice Situations.